Healthcare provider cultural competency and receptivity to colorectal cancer screening among African Americans. Issue 10 (26th November 2022) - Dawadi, Anurag; Lucas, Todd; Drolet, Caroline E.; Thompson, Hayley S.; Key, Kent; Dailey, Rhonda; Blessman, James
ABSTRACT: African Americans suffer disproportionately from colorectal cancer (CRC), due in part to disparities in CRC screening. Better understanding culturally relevant psychosocial factors that impact CRC screening is therefore critical. This study examined how African Americans' perceived cultural competency of their physician is associated with receptivity to take-home stool-based CRC screening. CRC screening deficient African Americans ( N = 457) completed a patient-focused measure of perceived cultural competency and watched a brief video about CRC risks, prevention, and screening. Receptivity to stool-based CRC screening was measured using Theory of Planned Behavior (TPB) constructs . Participants were also given an opportunity to receive a no-cost at-home Fecal Immunochemical Test (FIT) kit, and we measured acceptance of this offer as a behavioral outcome (yes-no). Results showed that perceived cultural competency was associated with higher receptive attitudes, more favorable norms, greater perceived behavioral control towards stool-based screening, and also greater intentions to engage in FIT Kit screening ( p < 0.001). We also found significant indirect effects of perceived cultural competency on FIT kit uptake through intention-mediated pathways. This study provides crucial evidence that participants' perceived cultural competency may play an important role in preventive health behavior among racial minorities, including CRC screening uptake among African Americans.